EFFECT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PDAM TIRTAJATI CIREBON REGENCY - Maharani, Elistiana; Febriani Pratiwi, Dela; Ayu Hardjowikarto, Dharliana; Sunimah, Sunimah (Penerbit Lafadz Jaya, 2025)
This study intends to assess the effect of Organizational Citizenship Behavior (OCB) and work discipline on employee performance at PDAM Tirtajati Cirebon Regency. The research adopts a quantitative approach in its methodology that is associative in nature. Data were obtained using a questionnaire given to 119 employees who have worked for at least five years. The data processing process involved validity testing, reliability testing, classical assumption checking, and multiple linear regression analysis. The outcomes of this investigation reveal that OCB and work discipline, when analyzed individually, have a positive and significant influence on employee performance. Together, these two variables also contribute significantly to performance with the coefficient of determination (R²) reaching 78.9%. These findings indicate that strengthening voluntary behavior and maintaining high work discipline are crucial strategies to improve employee performance, especially in public service organizations such as PDAM Tirtajati.